Maternal, Neonatal, Child, Sexual and Reproductive Health Services in Kampala, Uganda - Burt, Jessica; Ouma, Joseph; Amone, Alexander; Aol, Lorna; Sekikubo, Musa; Nakimuli, Annettee; Nakabembe, Eve; Mboizi, Robert; Musoke, Philippa; Kyohere, Mary; Namara, Emily; Khalil, Asma; et al. (medRxiv., 2021)
COVID-19 has impacted global maternal, neonatal and child health outcomes. We hypothesised that the early, strict lockdown which severely limited the movements of individuals in Uganda will have impacted access to services. An observational study, using routinely collected health data from Electronic Medical Records was carried out, utilising data from July 2019 to December 2020 in Kawempe district, Kampala. The mean and 95% confidence intervals were calculated pre-COVID (July 2019 – February 2020) and post-COVID (March-December 2020). The means were compared using t-tests, and the monthly totals analysed as to whether they lay within or outside the normal range, compared to the previous 9 months. Antenatal attendances decreased 96% in April 2020 and remain below pre-COVID levels. We found a rise in adverse pregnancy outcomes for Caesarean sections (5%), haemorrhages related to pregnancy (51%), stillbirths (31%) and low-birth-weight (162%) and premature infant births (400%). We noted a drop in neonatal unit admissions, immunisation clinic attendance and delivery of all vaccinations except measles. There was an immediate drop in clinic attendance for prevention of mother to child transmission of HIV (now stabilised) and an increase of 348% in childhood malnutrition clinic attendance. Maternal and neonatal deaths, immediate post-natal care and contraceptive provision remained within normal limits.The response to COVID-19 in Uganda has negatively impacted maternal, child and neonatal health, with the biggest and longest lasting impact seen in complications of pregnancy, stillbirths and low-birthweight infants likely due to delayed care-seeking behaviour. The decline in vaccination clinic attendance has implications for all vaccine-preventable diseases, with a cohort of infants currently unprotected. Further consideration of the impacts of restricting movement and limiting access to preventative services must be undertaken in responding to future pandemics if key maternal and child health services are to be maintained.
Keywords: COVID19, maternal health, child health, vaccines, neonates